SIMULATION STUDY OF LOW VELOCITY IMPACT ON SOLAR PHOTOVOLTAIC PANEL - MOHD SAIDI, AIMI AYUNI (2018)
The ground-mounted solar photovoltaic panel is very effective to be used as a large electricity generator in the remote sites or inaccessible areas. However, the ground-mounted solar photovoltaic panel is often exposed to the climatological natural disaster such as the thunderstorms, hailstones and also the sand-gusting. The small particles from these phenomenon with low velocity, will hit the solar photovoltaic panel. The objectives of this study are to develop a simulation model that can be used to study the low velocity impact on solar photovoltaic panel and to investigate the effect of low velocity impact on solar photovoltaic panels using Abaqus software. A model of solar photovoltaic panel is designed using Abaqus software and the simulation is run to study the effect of the low velocity impact on solar photovoltaic panels. The designed simulation is run and it is found that with different velocity of the impactor, the maximum forces of the impact are from the range of 1.200 kN to 1.800 kN, the mean forces of the impact are from the range of 0.080 kN to 0.700 kN and the absorption energies of the impact are from the range of 0.1 J to 1.2 J. With different size of the radius of the impactor, the maximum forces of the impact are from the range of 1.400 kN to 4.000 kN, the mean forces of the impact are from the range of 0.090 kN to 0.600 kN and the absorption energies of the impact are from the range of 0.1 J to 1.1 J. The higher the velocity of the impactor, the higher the mean force and the absorption energy. The bigger the size of radius of the impactor, the higher the mean force and the absorption energy.